General properties and applications of plasmids - Clewell, Don (Henry Stewart Talks, 2008)
Properties of plasmids that facilitate isolation, Basic analyses of plasmids, Restriction enzymes and their use as analytical tools, The important role of plasmids in recombinant DNA technology and genome analyses
Reviewed at 2023/04/16